Red Raíces: a pedagogical experience for environmental democracy from the regions of Colombia - Muñoz Ávila, Lina; Sánchez Jaramillo, Johana Fernanda; Iregui-Parra, Paola Marcela; Torres-Villarreal, María Lucía; Serna Mosquera, Laura Marcela (Revista de Derecho Ambiental, 2023)
This article objective is to unveil the challenges that the Colombian environmental and participative democracy faces after 30 years of the enacted Political Constitution of 1991, which consolidated the social state of law and the necessity of facing these through the strengthening of environmental and participative democracy and pedagogical experiences such as the Red Raíces, and educative and innovative educational project of the Grupo de Acciones Públicas (GAP) at Rosario University that contributes to strengthen the rights to access to justice and participation through the legal training of youth from the regions, especially from those where barriers persist to access education legal and environmental education. As from the Red experience this work concludes that the obstacles to fortify environmental democracy, proposed by the Constituent Assembly of 1991, persist and the legal clinics with their theoretical and practical training for new generations can strengthen the rights to information, public participation and environmental justice pillars of environmental democracy. This essay was elaborated based on a qualitative methodology, for its flexibility, using doctrinaire, normative and juridical sources combined with Red Raíces presentation.